2018
DOI: 10.1186/s13104-018-3983-4
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infections and associated risk factors in patients with diabetes mellitus; case control study in North West Tigray, Ethiopia

Abstract: ObjectiveThe objective of this study was to determine the seroprevalence of Hepatitis C virus among patients with Diabetes mellitus and healthy control groups in North West Tigray. Blood samples from each study subject was tested for Hepatitis C virus by using anti Hepatitis C virus antibody rapid test kits and confirmed using enzyme linked immuno sorbent assy.ResultThe overall seroprevalence of Hepatitis C virus, Hepatitis C virus among diabetic and non diabetic study subjects were found (16.7, 28, and 6) % r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Current or previous sexual activity (P = 0.003) was associated with seropositivity which was consistent with a study by Okafor et al [ 24 ] and positive HIV status (P = 0.012) was also associated with seropositivity which was also consistent with work done by Gebrekristos et al in Ethiopia [ 39 ], where immunosuppression was associated with anti-HCV seropositivity. Other risk factor associations with seropositivity included previous maternal positive test for anti-HCV (P = 0.000) and history of FGM or circumcision (P = 0.032).…”
Section: Discussionsupporting
confidence: 91%
“…Current or previous sexual activity (P = 0.003) was associated with seropositivity which was consistent with a study by Okafor et al [ 24 ] and positive HIV status (P = 0.012) was also associated with seropositivity which was also consistent with work done by Gebrekristos et al in Ethiopia [ 39 ], where immunosuppression was associated with anti-HCV seropositivity. Other risk factor associations with seropositivity included previous maternal positive test for anti-HCV (P = 0.000) and history of FGM or circumcision (P = 0.032).…”
Section: Discussionsupporting
confidence: 91%
“…This result could be justified not only by the high representation of women in society but also by their greater attendance at healthcare facilities. The majority of participants had a primary level of education (38%), this is in line with the study by Gebrekristos et al, in Ethiopia, which reports a proportion of 36.5% of participants with a primary level of education [16]. This justifies the fact that most respondents had heard of hepatitis B and C, but did not know the mode of transmission.…”
Section: Discussionsupporting
confidence: 88%
“…There are number of studies suggesting the possible positive association between the chronic HCV infection and DM. 17 The study conducted by Gebrekristos et al, 15 manifested that out of 77 (16.7%) seroprevalence HCV, major proportion HCV was found among patients with DM being 64 (28%) versus 13 (6%) in other patients without DM. In another study, 200 patients recruited from UK for a prospective study revealed the higher incidence of chronic HCV infection among patients with DM.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, it is not surprising that 70% patients with cirrhosis have impaired glucose tolerance and relatively fewer patients develop overt DM. 15 Insulin resistance, hyperinsulinemia and hyperglucagonemia form the underlying basis of this abnormal glucose metabolism. The patients with advanced CLD are at risk to develop hyperglycemia even with usual doses of steroids or interferon.…”
Section: Discussionmentioning
confidence: 99%